FAKTOR-FAKTOR YANG MEPENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Maulana, Ilham Ahmad (KRISNA: Kumpulan Riset Akuntansi, 2020)
In the last 10 years the realization of tax revenue has always never reached the target. One indication is always not achieving the tax target because there is tax aggressiveness carried out by the company. Tax aggressiveness is the act of lowering taxable income through tax planning activities, both legal and illegal. In this study aims to determine and analyze how the influence of Capital Intensity, Profitability, Leverage, Company Size and Inventory Intensity on Tax Aggressiveness. The population of this study are all property and real estate companies listed on the IDX. Sampling used a purposive sampling method to obtain 34 companies. Analysis of the data in this study uses multiple linear regression analysis. The results of this study found that the Capital Intensity, Profitability, and Inventory Intensity variavel affect Tax Aggressiveness, while Leverage and Firm Size do not affect the Tax Aggressiveness. The benefit of this research is to develop theories and knowledge in the field of accounting, especially in taxation related to tax aggressiveness and for investors can be considered when investing in order to avoid companies that do tax aggressive actions.